Determinants of Income Inequality in East Africa: The Role of Gendered Foreign Aid - (:unkn) unknown (My University, 2024)
This manuscript investigates the impact of gender-focused foreign aid on income inequality in East Africa, a topic with limited existing research. This research adds value by providing practical recommendations for policymakers to enhance the effectiveness of aid programs in fostering economic equity through targeted interventions. Using the Generalized Method of Moments (GMM) on panel data from three East African countries for over a decade provides robust evidence that gender-sensitive aid can significantly reduce income inequality. Our findings indicate that gendered aid, education and government expenditure were the driving force towards lower income inequality. Additionally, trade openness and inflation rates reduce income inequality in sampled countries, though insignificant. In contrast, the findings provide evidence that high economic growth tends to increase income inequality in East Africa and support evidence of positive channels. The major findings suggest that, in general, gendered aid does reduce income inequality. We observe that there is a need for more focused efforts and balanced aid to achieve equality goals. Increased focus and aid allocation on sectors like agriculture, digital economy, supply chains and transport can enhance women's access to opportunities and economic diversification, but a declining focus on health and education could undermine gains in their well-being.
Keywords: African Research